Preparation of PVdF-HFP based zinc ion conductor and its application in rechargeable zinc batteries / Suraya Sulaiman - Sulaiman, Suraya (Research Management Institute (RMI), 2010)
Polymer is an important constituent of polymer gel electrolytes (PGE) along with salt and solvent. The salt provides ions for conduction and the solvent helps in the dissolution of the salt and also provides the medium for ion conduction. In this study, ethylene carbonate (EC) and propylene carbonate (PC) containing different concentration of zinc triflate Zn2(CF3S03)2 salt were prepared to form liquid electrolyte. The optimum percentage of salt and plasticizer that gave the highest value of electrical conductivity of sample was determined. Impedance spectroscopy technique was carried out in order to determine the electrical conductivity value. The highest conductivity value of liquid electrolyte was 1.86 x 10" S/cm for 0.5M zinc triflate at room temperature. PGE was prepared by adding the highest conductivity value of liquid electrolyte with polymer host PVdF-HFP at room temperature, and the preparation conditions were optimized in view of ionic conductivity of the gel. The highest conductivity of PGE is 3.62 x 10ˉ3 S/cm. Finally, the highest conductivity plasticizer sample was used to fabricate battery. Battery was characterized using the open-circuit voltage and charge-discharge.